Electroactive polymers : advances in materials and devices : selected, peer reviewed papers from CIMTEC 2012-4th International Conference on Smart Materials, Structures and Systems, June 10-14, 2012, Terme, Italy - Vincenzini, P., 1939-; Skaarup, Steen (Advances in science and technology (Faenza, Italy), 2013)
The 14 peer-reviewed papers collected here together offer a plenitude of up-to-date information on ""Electroactive Polymers: Advances in Materials and Devices"". The papers are conveniently arranged into: Chapter 1: EAP Materials and Analysis of Physical Mechanisms, Chapter 2: Device Development and Applications. Review from Book News Inc.: Vincenzini (World Academy of Ceramics, Italy) and Skaarup (Technical U. of Denmark) collect 14 papers from Syposium C, ""Electroactive Polymers: Advances in Materials and Devices, "" of CIMTEC 2012, the Fourth International Conference on ""Smart Materials, S